1996
DOI: 10.1097/00005110-199604000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an Interdisciplinary Patient Care Team

Abstract: The authors describe how an interdisciplinary team used skills in communication and collaboration to improve patient care on a busy surgical service. A major goal was to establish and maintain continuity of care in the face of decreasing lengths of stay and increasing patient acuity. The authors share their insight about designing and supporting a successful interdisciplinary patient care team and discuss how their experiences relate to concepts such as case management and career development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…When interdisciplinary teams work well together, there is an increase of positive and measurable patient outcomes. Such teams design practices which integrate communication among members so that when these strategies are consistently practiced by team members, there are positive outcomes for practitioners and patients [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…When interdisciplinary teams work well together, there is an increase of positive and measurable patient outcomes. Such teams design practices which integrate communication among members so that when these strategies are consistently practiced by team members, there are positive outcomes for practitioners and patients [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…It is now increasingly common for healthcare organizations to employ interdisciplinary teams for more comprehensive diagnosis and treatment of patients as in other contemporary organizations (Cott, 1998). In line with other settings (Applebaum & Batt, 1994;Hill, 1982), research within healthcare organizations suggested that team-based working leads to enhanced equity, efficiency, and clinical quality in healthcare settings, for instance improved overall care (Cooke, 1997) and coordination of care (McHugh et al, 1996) for patients, and decreased length of patients' hospital stay (Wieland, Kramer, Waite, & Rubenstein, 1996). In addition to patient outcomes, team-based working is also related to reduced healthcare costs (Eggert, Zimmer, Hall, & Friedman, 1991).…”
mentioning
confidence: 98%
“…This kind of practice culture in healthcare organizations or hospitals establishes the validity and reliability of the construction process of PCN and the generalizability of our research findings. There are also studies in current literature where researchers consider patient log book as a medium that facilitates collaboration among the hospital staff .…”
Section: Discussionmentioning
confidence: 99%